B217 Regional blockades for lower limb amputation as anaesthetic approach: two cases report. (11th August 2022) - Suarez, AM; Moyano, J; Escobar, S; Santoyo, M
Abstract : Background and Aims: After lower limb amputation most patients experience severe acute pain (57% to 100%), multiple peripheral nerve blockades have been proposed as an anesthetic/analgesic technique(1). Sciatic nerve block (SNB) and femoral nerve block (FNB) are regional approaches for those at risk to develop postsurgical chronic pain, including phantom limb pain(1 2). This regional approach may improve the outcomes compared with general anesthesia alone in high-risk patients by blunting surgery-related inflammation(1 3). The aim of this report is to show the effect of lower limb blockades as a sole anesthetic technique in two patients who underwent successful limb amputation. Methods: Two cases of unilateral transtibial amputation in ASA III elderly patients (severe cardiovascular, pulmonary, and peripheral vascular diseases). Patient informed consent was obtained. Patients who underwent peripheral nerve blockades (sub gluteal sciatic, femoral at the inguinal crease, and femora-cutaneous lateral nerve) were performed under a standardized ultrasound technique. Intravenous opioid Patient-controlled analgesia and non-opioid analgesics were administered. Results: Both patients and surgeons reported proper surgical conditions and long-lasting postoperative analgesia (72 hours). There were no requests for additional analgesia and PCAs use was minimum. Patients reported satisfaction with analgesic treatment. Conclusions: Multiple peripheral nerve blockades are an efficient and safe alternative for lower limbs amputation, being more convenient and safer than general anesthesia and neuraxial anesthesia in selected patients. A good performance in ultrasound-guided regional anesthesia is required(2). Multiple peripheral nerve blockades are recommended as an anesthetic technique for lower limbs amputations in selected patients.